O DIREITO COLETIVO DE FISCALIZAÇÃO E PARTICIPAÇÃO NA POLÍTICA PÚBLICA AMBIENTAL: O CONSELHO MUNICIPAL DE DEFESA DO MEIO AMBIENTE DE RIBEIRÃO PRETO NA QUALIDADE DE ESPAÇO PÚBLICO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This study aims to analyze the Municipal Council for the Defense of the Environment of the Municipality of Ribeirão Preto (COMDEMA) as a public space for the effective exercise of participatory democracy, addressing the institutional functions of COMDEMA and its understanding of the quality of public space for participation of civil society in the inspection and formulation of municipal public policies in the environmental field.